2009
DOI: 10.1111/j.1945-5100.2009.tb01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation textures, mechanisms of formation of high‐pressure minerals in shock melt veins of L6 chondrites, and pressure‐temperature conditions of the shock events

Abstract: Abstract-The high-pressure polymorphs of olivine, pyroxene, and plagioclase in or adjacent to shock melt veins (SMVs) in two L6 chondrites (Sahara 98222 and Yamato 74445) were investigated to clarify the related transformation mechanisms and to estimate the pressure-temperature conditions of the shock events. Wadsleyite and jadeite were identified in Sahara 98222. Wadsleyite, ringwoodite, majorite, akimotoite, jadeite, and lingunite (NaAlSi 3 O 8 -hollandite) were identified in Yamato 74445. Wadsleyite nucleat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 53 publications
(125 reference statements)
2
42
0
1
Order By: Relevance
“…The chemical composition of the poorly crystallized material is identical to ðMg;FeÞSiO 3 . Although clinopyroxene, majorite, and akimotoite are candidates for such a composition, they occur in shocked meteorites usually in the crystalline state (4,14,22). Hence, the glass with the ðMg;FeÞSiO 3 composition is unlikely any of the three mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical composition of the poorly crystallized material is identical to ðMg;FeÞSiO 3 . Although clinopyroxene, majorite, and akimotoite are candidates for such a composition, they occur in shocked meteorites usually in the crystalline state (4,14,22). Hence, the glass with the ðMg;FeÞSiO 3 composition is unlikely any of the three mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…Jadeite crystallite assemblages contain many 'particle-like' materials as shown in Figure 3B. Ozawa et al (2009) described that the 'particle-like' material was silica-rich amorphous material, and proposed that original albite feldspar transformed to jadeite and the amorphous material. Similar jadeite crystallite assemblages were also observed in the albite feldspar (Ab 83-85 An 10 Or 5-7 ) grains entrained in the shock-melt veins of Sahara 98222 L6 ordinary chondrite .…”
Section: Textural Variations Of Jadeite In Shocked Meteoritesmentioning
confidence: 99%
“…Their typical textures are shown in Figure 4. Ozawa et al (2009) suggested that the particle-like and stringer-like materials may be composed of silica-rich amorphous materials. Further detail investigation on jadeite in shocked ordinary chondrites was conducted using focused ion beam (FIB)-assisted TEM and XRD patterns together with FE-SEM and Raman spectroscopy.…”
Section: Textural Variations Of Jadeite In Shocked Meteoritesmentioning
confidence: 99%
See 2 more Smart Citations